Increased ischemic stroke, acute coronary artery disease and mortality in patients with granulomatosis with polyangiitis and microscopic polyangiitis. (January 2019) - Mourguet, M.; Chauveau, D.; Faguer, S.; Ruidavets, J.B.; Béjot, Y.; Ribes, D.; Huart, A.; Alric, L.; Balardy, L.; Astudillo, L.; Adoue, D.; Sailler, L.; et al.
Abstract: Objective: The aim of our study was to assess major cardiovascular event incidence, predictors, and mortality in ANCA-associated vasculitis (AAV). Methods: We conducted a retrospective cohort study of all GPA or MPA, according to Chapel Hill Consensus Conference classification criteria, diagnosed between 1981 and 2015. Major cardiovascular event was defined as acute coronary artery disease, or ischemic stroke, or peripheral vascular disease requiring a revascularization procedure. We calculated the comparative morbidity/mortality figure (CMF) and we used Cox proportional hazards regression models to assess the risk of coronary artery disease, ischemic stroke associated with AAV, after adjusting for covariates. Results: 125 patients, 99 GPA (79, 2%) and 26 MPA (20, 8%), were followed 88.4 ± 78.3 months. Ischemic stroke incidence was four times higher than in the general population (CMF 4, 65; 95% CI 4, 06-5, 31). Coronary artery disease incidence was four times higher than in the general population (CMF 4, 22; 95% CI 1, 52-11, 68). Smoking habits and history of coronary artery disease were strongly associated with coronary artery disease occurrence (adjusted HR 8.8; 95% CI 2.12–36.56, and adjusted HR 10.3; 95% CI 1.02–104.5, respectively). ENT flare-up was an independent protective factor for coronary artery disease occurrence. We did not identify factors significantly associated with stroke occurrence. The age-adjusted mortality rate was 22.5 per 1000 person-years. Mortality in AAV was 1.5 times higher than in the general population (CMF 1.56; 95% CI 1.34–1.83). Conclusion: AAV have a significantly increased risk of mortality, ischemic stroke, and coronary artery disease. Highlights: Patients with AAV have a four times more risk of ischemic stroke or coronary artery disease that in the general population. Cardiovascular mortality in associated-ANCA vasculitis (AAV) patients is 1.5 times more than in the general population. Monitoring for this complication and vigilance in modifying risk factors are warranted in this patient population.